State of the Heart: Neurophysiological and Neuropsychological Sequelae of Out-of-Hospital Cardiac Arrest In Good Outcome Survivors - Byron-Alhassan, Aziza (Université d'Ottawa / University of Ottawa, 2020)
Survivors of out-of-hospital cardiac arrest (OHCA) are at risk for hypoxic-ischemic brain injury, which can cause a broad range of effects from death to subtle cognitive impairment. This dissertation includes two studies of OHCA patients who had made good neurological recovery after OHCA. In both studies, patients were evaluated near the time of hospital discharge, when crucial decisions such as rehabilitation plans are made. In addition, OHCA survivors were compared with a myocardial infarction (MI) control group in both studies. Study 1 explored the frequency, severity, and predictors of cognitive dysfunction in OHCA survivors, and characterized the cognitive profile of these patients using a comprehensive neuropsychological battery. Study 2 explored grey matter volume (GMV) in OHCA survivors, MI patients, and healthy controls, and correlated these with cognitive dysfunction and important clinical characteristics (e.g., downtime). While OHCA patients performed poorer on cognitive testing than MI patients, both groups showed decreased GMVs compared to healthy controls. OHCA survivors who have had good neurological recovery may still face significant challenges when they re-engage in difficult cognitive tasks post-arrest. To date, these cognitive issues after OHCA have been somewhat overlooked in Canada's healthcare system. A better understanding of hypoxic-ischemic brain injury among survivors will aid in the promotion of targeted interventions and rehabilitation efforts, and may help clinicians predict those who are most at risk.
Keywords: cardiac arrest; neuropsychology